Studi Literatur: Hubungan Pemberian ASI dengan Kejadian Ikterus Neonatorum - Latiefatus Salaamah; Jamhariyah Jamhariyah; Riza Umami; Kiswati Kiswati (Malang Journal of Midwifery (MAJORY), 2022)
Neonatal jaundice is one of the causes of neonatal death in Indonesia. Jaundice can be caused by the accumulation of unconjugated bilirubin, one of which is due to lack of breastfeeding in the first week of birth. This literature study aimed to determine the relationship between the frequency of breastfeeding and the incidence of neonatal jaundice. This literature study was conducted by determining the topic and formulating the PICOT. The criteria for articles reviewed by articles spanning the years 2016-2020 and using the Google Scholar database. The keywords used were “ASI” AND “Icterus neonatorum” or “Breastfeeding” AND “Jaundice”. Based on a review of 5 research articles, it was found that if breastfeeding was carried out with a frequency of 8-12 times per day, newborns could experience physiological neonatal jaundice. A review of 4 articles showed that there was a relationship between breastfeeding and neonatal jaundice and 1 article showed that there was no relationship between breastfeeding and neonatal jaundice. The more frequent breastfeeding, the lower the possibility of neonatal jaundice. This shows the role of midwives and breastfeeding counselors in providing IEC during pregnancy and breastfeeding, breastfeeding practices include the position of the breast attachment, implementation of IMD in newborns without complications, and breastfeeding immediately after the baby is born, all of which can support the frequency of breastfeeding and reduce the incidence of neonatal jaundice Keywords: Breastfeeding, Neonatal Jaundice